Cesium Lead Bromide (CsPbBr3) Thin‐Film‐Based Solid‐State Neutron Detector Developed by a Solution‐Free Sublimation Process. Issue 12 (11th November 2020) - Fernandez‐Izquierdo, Leunam; Reyes‐Banda, Martin Gregorio; Mathew, Xavier; Chavez‐Urbiola, Iker Rodrigo; El Bouanani, Lidia; Chang, Joseph; Avila‐Avendano, Carlos; Mathews, Nini Rose; Pintor‐Monroy, Maria Isabel; Quevedo‐Lopez, Manuel
Abstract: The majority of solid‐state radiation sensors are predominantly single crystals. However, for low‐cost and large‐area device applications, thin films are a better option. The first evidence of neutron detection using a Gallium Oxide/Cesium Lead Bromide (Ga2 O3 /CsPbBr3 ) solid‐state diode enabled by an innovative close space sublimation (CSS) method that allows deposition of thick CsPbBr3 films is demonstrated. Furthermore, indirect neutron sensing is achieved using a 10 B layer for diodes biased at voltages as low as –5 V,  showing the potential for low‐power operation. The neutron response is enabled by the low leakage current (≈10 −8 A mm –2 ), rectification of ≈10 4, capacitance as low as 15 pF, and fast response of the Ga2 O3 /CsPbBr3 diode. The superior performance of the CsPbBr3 is due to the phase purity, stoichiometry control, and large single‐grain columnar growth of the films obtained by the CSS method. Abstract : A Ga2 O3 /CsPbBr3 solid‐state diode is developed and demonstrated as an indirect neutron detector. The observed device performance is achieved with the use of CsPbBr3 active layer with large grains grown perpendicular to the interface. The columnar growth is enabled with a novel solvent‐free close space sublimation method that allows CsPbBr3 film deposition in one step from single‐crystal source.